Effect of nanobubble water on medium chain carboxylic acids production in anaerobic digestion of cow manure - Liu, Yang; Ye, Xiaomei; Chen, Kequan; Wu, Xiayuan; Jiao, Lihua; Zhang, Hongyu; Zhu, Fei; Xi, Yonglan (Waste management (New York, N.Y.), 2024)
Nanobubble water promotes the degradation of difficult-to-degrade organic matter, improves the activity of electron transfer systems during anaerobic digestion, and optimizes the composition of anaerobic microbial communities. Therefore, this study proposes the use of nanobubble water to improve the yield of medium chain carboxylic acids produced from cow manure by chain elongation. The experiment was divided into two stages: the first stage involved the acidification of cow manure to produce volatile acidic fatty acids as electron acceptors, and the second phase involved the addition of lactic acid as an electron donor for the chain elongation. Three experimental groups were established, and air, H2, and N2 nanobubble water were added in the second stage. Equal amounts of deionized water were added in the control group. The results showed that nanobubble water supplemented with air significantly increased the caproic acid concentration to 15.10 g/L, which was 55.03 % greater than that of the control group. The relative abundances of Bacillus and Caproiciproducens, which are involved in chain elongation, and Syntrophomonas, which is involved in electron transfer, increased. The unique ability of air nanobubble water supplemented to break down the cellulose matrix resulted in further decomposition of the recalcitrant material in cow manure. This effect subsequently increased the number of microorganisms associated with lignocellulose degradation, increasing carbohydrate metabolism and ATP-binding cassette transporter protein activity and enhancing fatty acid cycling pathways during chain elongation. Ultimately, this approach enabled the efficient production of medium chain carboxylic acids.
Keywords: Electron transport; anaerobióza; Anaerobiosis; Nitrogen; dusík; Fatty Acids, Volatile; biodegradace; Hydrogen; Carboxylic Acids; Nanostructures; kyseliny karboxylové; vzduch; zvířata; hnůj; Biodegradation, Environmental; Manure; Air; nanostruktury; Fatty acid cycle pathway; Chain elongation; Cattle; Clostridiales; Anaerobic digestion; voda; skot; vodík; transport elektronů; Water; kyseliny mastné těkavé; Animals; Electron Transport; Nanobubble water